ANALISIS PENGARUH PENETRASI DISTRIBUTED GENERATION TERHADAP PROFIL TEGANGAN, SUSUT DAYA DAN KEANDALAN JARINGAN DISTRIBUSI TENAGA LISTRIK - , Didik Hadiyanto, S.T.; , Sarjiya, S.T., M.T., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Distributed generation (DG) is expected to play a key role in electric power system in the future. Distributed Generation (DG) provides an alternative to the traditional electricity sources i.e. oil, gas, coal, etc. and can also be used to enhance electrical power system. Nowaday, the development of DG mostly focus on renewable energy i.e. small hydro power, solar thermal, photovoltaic, biofuel, biomass, biogass, wind turbines etc. The DGs are becoming increasingly popular for their renewable energy, low emission and pollutions, low operations and maintenance cost, but not in investment cost. One of the main applications of DG is providing positive impact to the power system. Since the use of DG is getting developed and giving many advantages, it is very important to study its impact on distribution network operation. This research explores the impacts of installing DG on a rural distribution system. And it focuses on analyzing the impact of DG installation on distribution network operation including voltage analysis, electric losses and reliability of the system. At the first section, the voltage impacts of various DG penetration levels are explored. Secondly, the losses of the system are analyzed. Finally, the reliability analysis (SAIFI, SAIDI, CAIDI, ENS, and AENS) of the system is performed by installing DGs. A rural distribution system in Kulon Progo, DIY Province will be the object of this research. This Distribution was built using its one-line diagram in ETAP version 7.0.0 (Electrical Transient Analysis Program) to perform detailed voltage profile analysis and power losses analysis. The other software is Microsoft Excel 2007 to perform reliability evaluation. This research uses smallhydro power potential on Kalibawang irrigation canal for DGs. There are two locations of small-hydro power potential on the Kalibawang irrigation canal which has total potential capacities up to 1000 kW. A rural distribution system is 5th feeder of Wates distribution substation which reaches small-hydro power potential on Kalibawang irrigation canal. The development of small-hydro power potential in Kalibawang irrigation canal as DG with capacities up to 1000 kW, will give positive impact to 5th feeder of Wates substation : 1. Improve voltage profile of the system by 0,596 kV (2,98%). 2. Reduce power losses of the system by 92 kW (26,1%). 3. Improve reliability indices of the system (SAIDI by 14,31%, CAIDI by 14,31% and ENS by 14,04%)